Performance of rapeseed-mustard in India- a temporal analysis - PP Kumar; SV Ramana Rao; VK Choudhary; AK Koshta; MA Khan; ML Lakhera; I Krishna Teja (Journal of Oilseed Brassica, 2026)
The performance of rapeseed-mustard in India using time series data from 1967-68 to 2019-20 was examined. The totalperiod was divided into period I, II and III to analyze the trends, compound annual growth rate (CAGR), decompositionanalysis, instability analysis and impact of technological change in production of rapeseed-mustard. The study revealedthat performance of rapeseed-mustard during different periods was noteworthy. An upward increasing trend was evidencedfor area, production and yield in all the three periods signifying the progress of rapeseed-mustard while the CAGRanalysis revealed acceleration for area, production and yield. The decomposition analysis indicated that change inproduction of rapeseed-mustard were due to yield effect and area effect during period I; area expansion during period IIand; area effect and yield effect during period III. The crop was relatively stable with lower instability with regard to area,production and yield resulting to sustained production. Technological progress on production of rapeseed-mustardwas observed in periods I and III, while area expansion contributed to production growth in all the three periods.Technology regress was not evidenced in rapeseed-mustard indicating the power of technology(s) developed under theNational Agricultural Research and Education System. To increase the production of rapeseed-mustard, technologyassemblage is warranted in high area-low productivity districts; diversification to newer agro-eco regions and in selectedrice-fallow ecosystems. To task strides towards “Make in India” and “Atmanirbhar Bharat”, focus on value chains isimportant towards doubling of farmers income and for promoting rural entrepreneurship.